Bring your own encryption: balancing security with practicality. Issue 1 (January 2015) - Zhang, Hongwen
Abstract : Since the start of the 21st Century, security has emerged from scare-story status to become one of every IT user's biggest issues – as survey after survey confirms. Along the way a number of uncomfortable lessons are still being learned.